HATCHABILITY PERFORMANCE OF DIFFERENT COLOUR BROILER BREEDER STRAIN - Pandian, C; Omprakash, AV; Selvan, ST; Sudersan, A (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted to compare the fertility and hatchability of Nandanam broiler I, Nandanam broiler II and Nandanam broiler III at the age of 28-58 weeks maintained at Poultry Research Station, Tamil Nadu Veterinary and Animal Sciences University, Chennai-51. The per cent fertility, hatchability on eggs set, on fertile eggs and embryonic mortality were worked out. The mean per cent fertility of different colour broiler breeder strain were differed significantly (P<0.01). The Nandanam broiler II recorded significantly higher fertility and hatchability to total eggs set. The overall mean per cent hatchability to total and fertile eggs set of different colour broiler breeder strains were 72.51 ±1.0 and 85.37±0.75. Significant difference (P<0.05) were observed for mean per cent embryonic mortality, mean per cent dead in germ and dead in shell in different colour broiler breeder strain. The study concluded that reproductive performances were better in Nandanam broiler II and Nandanam broiler I than Nandanam broiler III.